Analisis Gerakan Literasi Sekolah Di SDN 2 Bangsri Selama Pertemuan Tatap Muka (PTM) Terbatas - Ana Muflikhah; F Shoufika Hilyana; Ika Oktavianti (PGSD Universitas Muria Kudus, 2022)
The purpose of this study is to analyze the implementation of School Literacy (GLS) at SDN 2 Bangsri during limited PTM. This study uses a qualitative approach to the type of phenomenological research. The subjects of this study were school principals, fourth grade teachers, and fourth grade students. Data obtained from observation, interviews and documentation. The validity of the data using triangulation of data sources. Data analysis used interactive analysis techniques with stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that SDN 2 Bangsri during the limited offline learning (PTM) continued to carry out the GLS but the implementation was less than optimal as in the habituation stage it was only done for 10 minutes and used theme books continuously, at the development stage students never wrote their reading results in journals, at the learning stage the teacher was less maximum in providing reference books to students.